GAMBARAN PERILAKU KONSUMSI PANGAN DAN STATUS GIZI LANJUT USIA DI KELURAHAN PEKAN TANJUNG PURA KECAMATAN TANJUNG PURA KABUPATEN LANGKAT TAHUN 2012 - Maulida Batubara; Ernawati Nasution; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Elderly is very susceptible to various diseases; therefore, elderly can be in perfect health if they are able to maintain optimum nutritional status and consume nutritious and varied foods. The aim of the research was to know the description of food consumption behavior and nutritional status of the elderly at Kelurahan Pekan Tanjung Pura, Tanjung Pura Subdistrict, Langkat District, in 2012. The research was descriptive with cross sectional design. The population was 607 elderly who were around 60 years old. The sample is using inclusive criteria with non-dementia criteria, did not lie down on the bed because of illness and were still able to stretch out their hand, obtained the sample of 108 people. The data were gathered by conducting interviews with questionnaires and food frequency forms. The result of the research showed that the respondents’ knowledge and attitude about consuming food was in the category of moderate, their eating pattern was in the category of good (83,3%), and their nutritional status was in the category of normal (47,2%). Some of them were in the category of more nutrition (20,4%), some of them were in the category of malnutrition (19,4%), and some of them were in the category of obesity (13,0%). It is recommended that elderly should be treated more properly through posyandu (integrated service post) by providing counseling and health promotion. This can be done by giving information about consuming good food by elderly. Keywords: Behavior, Food Consumption, Nutritional Status, Elderly